PARADIGMA PEMBELAJARAN TERINTEGRASI HOTS, 4C DAN TECHNOLOGY: SUATU KEHARUSAN BAGI SISWA - Yalvema Miaz (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2020)
With the development of technology in the 21st century it has been able to provide pro-active learning, easy to understand and comprehensive as a learning environment, so we need an integrated learning paradigm of HOTS, 4c and tecnology. The problem encountered in this study is that a small percentage of teachers have not used HOTS based question in the learning process that can improve students high-level thingking processes. The purpose of this study is to improve students high level thinking processes in the learning process.The type of research used is development using the Plomp model. The subjects in this study were teachers of Bukittingi City 02 Pilot School. The instrument in student and teacher observation sheets, interviews and learning tools this study produced a HOTS based student worksheet.